Synergistic catalytic effect of iron metallic glass particles in direct blue dye degradation. Issue 8 (21st April 2015) - Das, Santanu; Bandi, Venugopal; Arora, Harpreet Singh; Veligatla, Medha; Garrison, Seth; D'Souza, Francis; Mukherjee, Sundeep
Abstract: Abstract : We report on the high catalytic activity of iron based metallic glass (MG) particles in dissociating direct blue dye (C32 H20 N6 Na4 O14 S4 ) (DBD), a toxic water pollutant. We adopted high speed mechanical milling to activate the FeMG particles (of nominal composition Fe48 Cr15 Mo14 Y2 C15 B6 ) and optimized the morphology and the particle size to achieve complete degradation of DBD in less than 20 min. The surface morphology and the particle size of the activated particles were characterized using scanning electron microscopy and transmission electron microscopy. They were found to have corrugated edge like catalytically active surfaces after mechanical activation. The dye degradation rate of the activated MG powder was characterized via UV–visible absorption spectroscopy. The rate of dye degradation was significantly faster for the activated particles (within 20 min), compared to both pristine FeMG particles as well as elemental iron particles. In addition, the dye degradation mechanism was studied using Raman and infrared spectroscopy. The catalytically activated surfaces are believed to break the –C–H–, –C–N–, and –N=N– bonds, resulting in complete degradation of DBD.